The role of medical social workers in supporting social interaction development in children with autism: a qualitative descriptive study at a hospital - Agustinus Jehosua; Maya Yasinta Kondoy (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study explores the role of medical social workers in supporting the development of social interaction skills among children with autism in the Rehabilitation Medicine Unit of Prof. Dr. R.D. Kandou General Hospital, Manado. Using a qualitative descriptive design, data were obtained through in-depth interviews, participatory observation, and document review. Credibility was ensured through triangulation across data sources and methods, followed by member checking with key informants. The findings show that four roles of medical social workers contribute substantially to children’s social interaction development. As counselors, they facilitate parental acceptance and guide families in creating interactive home environments. As motivators, they strengthen parents’ emotional readiness and consistency in applying therapy strategies. Through the liaison role, they expand children’s access to early childhood education and peer-based social experiences. As consultants, they coordinate information and align approaches across interdisciplinary teams, enabling consistent social learning settings. The educator role remains limited due to staffing constraints. This study contributes by clarifying the mechanisms through which medical social workers enhance social interaction—primarily via parental engagement, therapy continuity, and increased social exposure—while offering context-specific insights from an Indonesian hospital-based rehabilitation setting.